Spatial and temporal variability of hyporheic invertebrate community within a stream reach of the River Bača (W Slovenia) - Nataša Mori; Anton Brancelj (Natura Sloveniae)
We studied spatio-temporal distribution of hyporheic invertebrate community at the stream-reach scale in the River Bača on three sampling occasions (January, March, May) in 2005. On each sampling occasion, invertebrates were collected from the shallow hyporheic zone (RB1; depth 30-60 cm, 3 replicates), and deeper hyporheic zone (RB2; depth 60-90 cm, 2 replicates) in the river bed, and adjacent gravel bar (GB; depth 60-90 cm, 3 replicates) using Bou-Rouch piston pump. Concurrently, temperature, conductivity and oxygen were measured in the surface water and in hyporheic water at each sampling station. Differences in hyporheic community between dates and habitats were analysed by using two-way ANOVA (dates and habitats as fixed factors) and explored by principal component analysis (PCA). Altogether, 21,657 specimens from 63 taxa were collected. Cyclopoida juveniles, Leuctra sp. (Plecoptera), Chironomidae (Diptera), Acanthocyclops vernalis (Fischer, 1853) and Diacyclops languidus (G. O. Sars, 1863) were the most abundant in the samples. Two-way ANOVA showed significant differences between habitats (RB1 and GB), but no differences between dates when using taxonomic richness as dependent variable. No differences between habitats and dates were calculated when invertebrate densities were applied. PCA of hyporheic invertebrate data showed a gradient in community composition from shallow hyporheic zone (RB1) to deeper hyporheic zone (RB2) and gravel bar (GB). The differences were most probably due to different sediment composition in the studied habitats and less frequent disturbances due to floods in deeper layers and lateral gravel bars.